Penney’s game between many players - Zajkowski, Krzysztof (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2014)
We recall a combinatorial derivation of the functions generating the probability of winning for each of many participants of the Penney game and show a generalization of the Conway formula for this case
Didactics of Mathematics, 2014, Nr 11 (15), s. 75-83
Keywords: Penney’s game; probability-generating functions; Conway’s formula